A arquitetura de paz de Gana sob um quadro de infraestruturas para a paz - Araújo, Suerda Gabriela Ferreira de (2018)
This research investigates whether there has been a process of transition from informal to formal Infrastructure for Peace (I4P) that originated Ghana’s National Peace Architecture (GNPA). It is based on the hypothesis that there were local processes of conflict and peacebuilding, notably in the three regions of north Ghana (Northern, Upper East and Upper West), which were determinant in the configuration of this Architecture. North Ghana is adopted as a spatial delimitation, because this region has been plagued by a myriad of conflicts interrelated to multiethnic contexts. The period from 1994 to 2017 was established as a time clipping because it includes the conflict between the ethnic groups of Nanumba and Konkomba, which was decisive for the emergence of initiatives for peace originated by Civil Society – especially the formation of the Consortium among NGOs in the decade of 1990, the development of the Center for Conflict Transformation and Peace Studies (CECOTAPS) and the structuring of National Peace Council – and the deadline of the Five Year Strategic Plan for the National Peace Council (2013-2017). Methodologically, this research adopts a qualitative, exploratory approach and the semi-structured interview technique, applied to the case study of the GNPA. For organizational purposes, four specific objectives were established: 1) to present the conceptual perspectives on Infrastructures for Peace; 2) to contextualize the evolution of the State, Civil Society and the interrelation of the causes of conflicts in the north region; 3) to understand Ghana's National Peace Architecture; and 4) to analyze the process of configuring the Ghana Peace Architecture under an I4P framework. From them, the discussion is constructed and distributed in four chapters.